A note for global existence of a two-dimensional chemotaxis–haptotaxis model with remodeling of non-diffusible attractant. (31st August 2018) - Ke, Yuanyuan; Zheng, Jiashan
Abstract: In this paper, we study the following coupled chemotaxis–haptotaxis model with remodeling of non-diffusible attractant in a bounded smooth domain with zero-flux boundary conditions, where χ, ξ and η are positive parameters. Under appropriate regularity assumptions on the initial data, by developing some L p -estimate techniques, we prove the global existence and uniqueness of classical solutions when, where μ is the logistic growth rate of cancer cells. This result removes the additional restriction on μ, where μ is sufficiently large in Pang and Wang (2017 J. Differ. Equ . 263 1269–92) for the global existence of solutions.